Parallel Implementation of the Algorithm to Compute Forest Fire Impact on Infrastructure Facilities of JSC Russian Railways; Algorithms; Vol. 14, iss. 11 - Baranovskiy N. V. Nikolay Viktorovich (2021, 2021)
Title screen